Fingerprint Technology and Sustainable Development - Utzhanova, Assiya (European Journal of Sustainable Development, 2016)
This paper explores to what extent fingerprint technology is reliable in technical, social and environmental aspects. Beginning from its history, application in business to how it’s modelled, statistical analysis on probability of mismatch, general overview of its effect on environmental sustainability, and attitudes towards fingerprint technology in society. Assessing the reliability of automated biometrics is important because of its application in business for security and user authentication purposes. It increases environmental awareness. Usage of fingerprint technology provides business opportunities that substitute traditional systems of credit card, written time-attendance records, and cash. It leads to sustainable development by using minimum resources; compared to other systems its application reduces production of plastic, paper consumption and contributes by energy and operational efficiency. Statistical analysis of fingerprint technology in framework of binomial, normal and Poisson distributions strengthens the reliability of fingerprint system. Source of the minutiae points used to analyze fingerprint characteristics is image of personal fingerprint. Statistical tests show that the accuracy may be improved. If the number of minutiae points increases, the probability of mismatch: type 1, type 2 errors decreases. Real-time experiments tested efficiency of system and provided data for hypothesis tests that challenged uniqueness of fingerprints. Social and ethical issues related to fingerprint recognition system were analyzed by conducting survey. Insecure storage of fingerprint image implies risk to the privacy of stakeholders, thus the system is not completely reliable for wider application. Accurate system design and improvement of such imperfections will generate more trust by stakeholders that will guide further towards sustainable development. Key words: The reliability of fingerprint technology in user authentication, its application in business and impact on environmental sustainability.